PEMAHAMAN PAJAK DAN AKUNTABILITAS PARTAI POLITIK MELALUI KKNI PADA PEMAGANGAN MAHASISWA FISIP UNIVERSITAS UDAYANA - Zuryani, Nazrina; Suka Arjawa, IGBP; Ali Azhar, M (PIRAMIDA; Vol 12 No 1 (2016), 2016)
Newly stated Indonesian Qualification Framework (IQF) set as a background to develop the curriculum and therefore students of Faculty of Social and Political Sciences (FISIP) at Udayana University as part of active population do intenship to recognize the government institutions work patterns. The textbooks become ‘social spirit’ (Etzioni in Poloma, 2013: 355) in Works Integrated Learning/WIL as research methodology. The internship evaluated to measure workers well understood taxes and procedure of political parties’ accountability. This 2016 year, there were 62 students from departments of Public Administration, Political Sciences and Sociology at Udayana University to study two textbooks of ‘Population & Taxes’ and ‘Political Parties’ Accountability’ in order to do the internship ten hours at each institutions after their middle exam. The internship was measured by survey of student’s perception, so as pre and post test before and after they go to the internship places. Hypothesis test shows that internship significantly influential to increase student achievement to understand the pattern of work at each institutions by T Paired Test resulting mean deviation 2.46 before internship to 4.66 after that. Male students (34 students from three departments) are having better scores for both pre and post-test in comparison to 28 female students. The score of post-test was the combination of score from lecturers and adjunct team from each institutions (Madya Tax Office and 4 Pratama Tax Offices together with the city of Denpasar Commision of Election and provincial Commission of Election offices). Student’s perception of 78. 9 percent was said that fiscal desentralisation was based on the Law No. 22 year 1999 and 86. 8 percent perception of students stated that low obedience of tax payer’s cause by combination of population dishonesty on income reporting, apatism and low tax socializing toward social welfare. Internship at the Election Commission offices resulting 76.9 perception of student stated that depolitification of parties taken place while 42.6 percent intern’s perception was said that no political parties had giving public information nor there was political education taken place perceived by half of interns. Unlike the internship in 2015, there was 85 internship participants involving 10 adjunct institutions, this year, internship taken place in the provincial tax offices (5 KPP), the Election Commission at city of Denpasar so as provincial office. In the future, it was recommended that internship length will be longer to increase professional competence of FISIP Udayana University students. Thus, beside the obedience of tax payment of students will be increasing, those alumni of FISIP Udayana University can become the tax or political paarties consultants that put ahead the welfare of population.
Keywords: Active population; Internship/Work Integrated Learning/WIL; professional Competence; Textbooks on ‘Population & Taxes’ and ‘Political Parties’ Accountability’